1999
DOI: 10.1016/s0029-7844(99)00300-2
|View full text |Cite
|
Sign up to set email alerts
|

Weekly administration of prostaglandin E2 gel compared with expectant management in women with previous cesareans

Abstract: Although its safety was confirmed for outpatient use, weekly doses of intracervical PGE2 did not improve the likelihood of vaginal births after cesareans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In our study the rate of uterine rupture after prostaglandin induction of labour with or without previous Cesarean was 2.5% and 0.033%, respectively. This is similar to the data shown by other investigators [10][11][12][13][14][15][16]. The risk of uterine rupture is influenced by many factors including birth weight, gestational age, race, country and maternal characteristics [17,18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study the rate of uterine rupture after prostaglandin induction of labour with or without previous Cesarean was 2.5% and 0.033%, respectively. This is similar to the data shown by other investigators [10][11][12][13][14][15][16]. The risk of uterine rupture is influenced by many factors including birth weight, gestational age, race, country and maternal characteristics [17,18].…”
Section: Discussionsupporting
confidence: 90%
“…There are no recent randomised controlled trails of labour induction in women with previous cesarean section [12]. There is one controlled randomised study comparing weekly administration of prostaglandin gel to expectant management in women with prior cesarean delivery [13]. However, this is not applicable to majority of patients who require induction due to various medical and obstetric reasons where pregnancy should be terminated within 24-48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six studies [3045, 48, 5058] (90%) examined the effects of at least one pharmacologic agent on VBAC rates, including prostaglandins, oxytocin, mifepristone and epidural analgesia. Ten studies [31, 33, 43, 4649, 53, 54, 57] (34%) examined non-pharmacologic or mechanical methods (membrane sweeping, amniotomy, balloon devices) in at least one intervention arm.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies reporting rupture or dehiscence, three [32, 45, 50] (10%) also reported uterine hyper-stimulation and three [41, 42, 44] (10%) also reported uterine atony; these outcomes were not included in analyses as they were considered clinically-related but distinct from the review’s outcomes of interest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation